2022
DOI: 10.23887/jere.v6i4.47747
|View full text |Cite
|
Sign up to set email alerts
|

How does Entrepreneurial Education Promote Medical Students' Entrepreneurial Orientation?

Abstract: Entrepreneurial education is a carefully planned process that leads to acquiring entrepreneurial capacity and competence, equipping students with the knowledge, skills, and motivation to drive entrepreneurial success. Many goals are achieved by organizing entrepreneurial education and promoting entrepreneurial orientation. In reality, only a few students choose a career as an entrepreneur, even though they have received an entrepreneurship education. Entrepreneurship orientation is crucial because it shows inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Various previous studies have shown the importance of entrepreneurial competence in encouraging the growth of entrepreneurial actors through education. Entrepreneurial competence is a skill or skill in managing the business being undertaken (Gieure et al, 2020), starting to plan carefully, determining who will carry out what tasks, carrying out the activity process, controlling the various activities carried out (Bismala et al, 2022). These skills are related to various fields of activity, such as in the management of finance, resources (including human resources), production and marketing.…”
Section: Ije-qqrmentioning
confidence: 99%
“…Various previous studies have shown the importance of entrepreneurial competence in encouraging the growth of entrepreneurial actors through education. Entrepreneurial competence is a skill or skill in managing the business being undertaken (Gieure et al, 2020), starting to plan carefully, determining who will carry out what tasks, carrying out the activity process, controlling the various activities carried out (Bismala et al, 2022). These skills are related to various fields of activity, such as in the management of finance, resources (including human resources), production and marketing.…”
Section: Ije-qqrmentioning
confidence: 99%
“…For this incident, the Ngawi District Health Office called the dentist who gave advice and extracted Nira's teeth, also asked for information from several doctors who treated the victim before she died. A dentist who performs tooth extraction at a private clinic owned by a dentist who is also one of the doctors at the Mantingan Regional General Hospital, Ngawi Regency, East Java (Bismala et al, 2024).…”
Section: Introductionmentioning
confidence: 99%